Attention-Deficit/Hyperactivity Disorder and Successful Completion of Anesthesia Residency: A Case Report. (February 2016) - Fitzsimons, Michael G.; Brookman, Jason C.; Arnholz, Sarah H.; Baker, Keith
Abstract : Cognitive and physical disabilities among anesthesia residents are not well studied. Cognitive disabilities may often go undiagnosed among trainees, and these trainees may struggle during their graduate medical education. Attention-deficit/hyperactivity disorder (ADHD) is an executive function disorder that may manifest as lack of vigilance, an inability to adapt to the rapid changes associated with anesthesia cases, distractibility, an inability to prioritize activities, and even periods of hyperfocusing, among other signs. Programs are encouraged to work closely with residents with such disabilities to develop an educational plan that includes accommodations for their unique learning practices while maintaining the critical aspects of the program. The authors present the management of a case of an anesthesia resident with a diagnosis of ADHD, the perspectives of the trainee, program director, clinical competency director, and the office of general counsel. This article also provides follow-up in the five years since completion of residency.